Mieszkanie, urbanizacja, spójność społeczna jako bariery zagospodarowania przestrzennego - Cesarski, Maciej (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2010)
This article deals with the development of space settlement as a potential barrier to proper spatial planning. As with spatial development, space settlement is geographically discontinuous and poses a number of risks to proper local, regional and global land use. This process, as seen in the European Union, clearly demonstrates the potential of urbanization to significantly reduce social cohesion. Territorial cohesion of the European Union is highly dependent on finding synergies between urbanization and the various characteristics of an area of social cohesion. This idea is an extension of and update to the thinking and practice of land use designed to achieve spatial order, which is based on spatial planning. Effects of phenomena and processes occurring in the area of the settlement as a basis for land use may therefore be important barriers to appropriate spatial management.